PENGARUH PENYIRAMAN SPRINKLER OTOMATIS BERBASIS MIKROKONTROLER DAN IOT (Internet Of Things) TERHADAP PERTUMBUHAN DAN HASIL KUALITAS TANAMAN SAWI PAKCOY (Brassica chinensis L) - irwan yudha pradana; Siti Asmaniyah Mardiyani; Sunawan Sunawan (AGRONISMA, 2020)
In vegetable production, especially in mustard, farmers in Indonesia are still using manual technology to maintain. With the technological advances of this century, known for a term of 4.0 that spawned the industrial revolution IoT (Internet of Things) as a solution to facilitate the work of farmers in the cultivation of plants. One form IOT use in agriculture is the Smart irrigation system with automatic sprinklers. This study aims to determine the effect of watering conventional models, sprinkle manual and automatic sprinkler-based microcontroller, and IOT (Internet of Things) on the growth, yield and quality pakcoy mustard plant (Brassica chinensis L). The experiments were conducted using a randomized block design (RAK) is simple with the treatment as a group. The factor used is the watering models with three levels with the hype that is watering, watering sprinkler watering the manual and automatic sprinkler-based microcontroller and IoT (Internet of Things). Each treatment was replicated eight times, and each test contains four plants. parameters measured were plant height, leaf number, leaf area, root length, plant fresh weight, dry weight of plant, texture, chlorophyll and carotenoids, total dissolved solids, vitamin C and water content. This study shows that there is no real consequence effect treatment watering models on all parameters observed. This means that the use of controlled sprinkle with IoT is not much different from the conventional way. The selection of a good sprinkler able to provide water evenly distribution of the mustard plant and IoT (Internet of Things) serves as the sprinkler controller.